Kinetic comparison of the sprint starts between youth and senior elite athletes - Graham-Smith, P.; Gallagher, L.; Brandner, C.; Hyun Ryu, J.; Palazzi, D. (ISBS Proceedings Archive (Michigan), 2018)
The purpose of this study was to identify differences in force, impulse and power characteristics in block starts and first two contacts between youth academy (n=20) and elite senior male sprinters (n=17). Senior sprinters were significantly faster out of the blocks with a horizontal velocity of 3.35 ±0.15 m/s compared to 3.14 ±0.16 m/s, leading to 10 m times of 1.64±0.045 s and 1.706±0.06 s respectively. Force application time of the arms, rear leg and front leg were significantly lower in the senior athletes (all p<0.0001). Relative peak vertical forces in arms, front and rear legs were all similar, but senior athletes generated greater peak horizontal force/BW (p<0.05) and power/BW from the rear leg (p<0.001). Understanding the function of the rear leg and implications on strength and technique will help to guide progression from youth to senior performance.